« Le goût amer de la couleur au Cap » - Chloé Buire (EchoGéo)
Cape Town is the “Mother-City” of the “Rainbow Nation”. Today the majority of its population is considered ‘Coloured’. The article disentangles the course of the construction of such a category which gather those who are « not White enough, not Black enough » (Adhikari, 2005). Stuart Hall’s notion of positioning helps to articulate two meta-narratives: the trauma caused by forced removals and the double-edge complex encapsulated by racial hierarchy. A short video portrait eventually shows how an individual pragmatically makes use of those scientific discourses. Eugene’s words, shaped in evangelist rhetoric are an invitation to question the status of our own scientific discourses and their role in building racial stereotypes.